2000
DOI: 10.1590/s0041-87812000000200004
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of medical courses in Brazil using student-completed questionnaires. Is it reliable?

Abstract: SUMMARY: Introduction:Debates about the quality of medical education have become more evident in the recent past, and as a result several different assessment methods have been refined for that purpose. The use of questionnaires filled out by medical students to assess the quality of lectures is one of the most common methods employed in our milieu. However, the reliability of this investigation method has not yet been systematically tested. The authors present the reliability of a specific form applied to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
(7 reference statements)
1
4
0
2
Order By: Relevance
“…For course evaluation, it was only one category that was associated with students’ scores, but six categories in class evaluations were significantly related to class scores. This result is in line with that of a preliminary study that compared prospective class assessment and retrospective course assessment [ 15 ]. In the study, the researchers concluded that evaluation immediately after classes was higher than retrospective course evaluation in quality, since medical students could not remember and rate every class in course evaluation.…”
Section: Discussionsupporting
confidence: 91%
“…For course evaluation, it was only one category that was associated with students’ scores, but six categories in class evaluations were significantly related to class scores. This result is in line with that of a preliminary study that compared prospective class assessment and retrospective course assessment [ 15 ]. In the study, the researchers concluded that evaluation immediately after classes was higher than retrospective course evaluation in quality, since medical students could not remember and rate every class in course evaluation.…”
Section: Discussionsupporting
confidence: 91%
“…However, this study still has some limitations. First, the course evaluation was administered at the middle of a curriculum; however, some studies suggested that continuous assessment during the courses brings up higher reliability ratings rather than the retrospective evaluation [1,20]. Second, the questionnaire is collected from the view of students, but it should be also accessible to teachers.…”
Section: Discussionmentioning
confidence: 99%
“…The reliability of retrospective student‐completed questionnaires has recently been discussed by Peluso et al. (2000).…”
Section: Discussionmentioning
confidence: 99%